User generated content: Cybernetic infographic visual narrative - Sufiana, Sufiana; Soewarlan, Santosa; Tinarbuko, Sumbo (Bulletin of Social Informatics Theory and Application, 2021)
User Generated content is a marketing strategy that emphasizes consumer-generated content, social media followers, and fans. The UGC trend has sparked interest in cyber media HaiBunda.com to integrate UGC in the process of creating infographic visual narratives. The infographic on HaiBunda.com is the result of media and UGC integration. The media provides a UGC space, for discussion, commenting, reading and viewing pictures. In practice, cybernetics visual narrative involves the role of information theory, control theory, and systems theory. Most of the UGC infographic channel visitors are millennial mothers who have interests in information about parenting patterns and child development. Can UGC readers interpret the visual infographic narrative, respond to and apply the values of daily morality in childcare? The purpose of the writing is to find out how millennial mothers interpret the visual infographic narrative. The qualitative method, Talcott Parsons' approach, is to see the meaning of the visual infographic narrative as a system, interrelation, has mutua influence to the media and readers. The results show that the visual narrative of HaiBunda.com's infographic with the theme “Tahukah Bunda” means educational and informative and contains moral values and the nature of women.